Decoding the Morphological Diversity in Two Dimensional Crystalline Porous Polymers by Core Planarity Modulation. (8th March 2016) - Halder, Arjun; Kandambeth, Sharath; Biswal, Bishnu P.; Kaur, Gagandeep; Roy, Neha Chaki; Addicoat, Matthew; Salunke, Jagadish K.; Banerjee, Subhrashis; Vanka, Kumar; Heine, Thomas; Verma, Sandeep; Banerjee, Rahul
Abstract: Two new chemically stable triazine‐ and phenyl‐core‐based crystalline porous polymers (CPPs) have been synthesized using a single‐step template‐free solvothermal route. Unique morphological diversities were observed for these CPPs [2, 3‐DhaTta (ribbon) and 2, 3‐DhaTab (hollow sphere)] by simply altering the linker planarity. A detailed time‐dependent study established a significant correlation between the molecular level structures of building blocks with the morphology of CPPs. Moreover, a DFT study was done for calculating the interlayer stacking energy, which revealed that the extent of stacking efficiency is responsible for governing the morphological diversity in these CPPs.